Effect of grinding wheel type and cooling method on grinding quality of SiCf/SiC ceramic matrix composites - Ben WANG; Jiajie TANG; Hongdi CHU; Qi ZHANG (Jin'gangshi yu moliao moju gongcheng)
ObjectivesSiCf/SiC fiber-reinforced ceramic matrix composites have been widely used in aerospace, nuclear energy, and high temperature structural parts due to their excellent high-temperature resistance, high specific strength, and oxidation resistance. However, due to the high hardness and brittleness of the material, its machinability is poor, and the traditional machining methods tend to cause serious tool wear, workpiece surface damage, and processing defects. Therefore, optimizing the grinding process to improve processing quality and efficiency has become one of the key issues in current research. Orthogonal grinding experiments of SiCf/SiC composites were carried out using electroplated diamond grinding wheels and sintered diamond grinding wheels, with or without coolant. Grinding force, surface roughness, and wear degree of grinding wheel were used as evaluation indexes to explore the effects of different grinding wheel types and cooling methods on the grinding quality of the material.MethodsAn orthogonal experimental design was used to systematically analyze the effects of different grinding wheel types (electroplated diamond grinding wheel, sintered diamond grinding wheel) and cooling methods (dry grinding, water cooling) on the grinding performance of SiCf/SiC composites. The experiment was conducted on a VMC850B CNC machine using a diamond grinding wheel with a diameter of 20 mm. Test parameters such as cutting speed, feed rate, and grinding depth were kept consistent to ensure comparability of results and scientific rigor of the experiment. During grinding, a KISTLER 9257B three-component dynamometer was used to measure tangential and radial grinding forces in real time to quantify the mechanical response under different grinding conditions. To evaluate the surface quality of the processed material, a ZYGO9000 white light interferometer was used to measure the surface roughness Sa of the workpiece. Three different regions of each sample were selected for measurement, and average values were taken to reduce the measurement error. Additionally, to analyze the wear mechanism of the grinding wheels, the wear morphology of the grinding wheel surface after grinding was observed using a VHX2000c ultra-depth-of-field three-dimensional microscope, and the failure modes of different grinding wheels under different grinding conditions were compared and analyzed.ResultsGrinding wheel type and cooling method have a significant effect on the grinding performance of SiCf/SiC composites. The grinding force of the sintered diamond grinding wheel is lower than that of the electroplated diamond grinding wheel, which is attributed to the higher abrasive retention and wear resistance of the sintered diamond grinding wheel. Compared with dry grinding, the grinding force is reduced under water-cooled conditions, indicating that the coolant can alleviate friction and heat accumulation during grinding to a certain extent, thereby reducing grinding force. At the same time, the sintered diamond grinding wheel can obtain lower surface roughness of the workpiece, the surface of the workpiece after processing is smoother, and the micro-defects such as cracks and tears are also significantly reduced. Furthermore, water-cooled assisted grinding can effectively reduce the surface roughness of workpiece and further improve the surface quality of workpiece, indicating that coolant positively influences surface integrity. The main wear form of the sintered diamond grinding wheel is the normal wear of abrasive particles, shweing strong abrasive retention and overall durability. In contrast, the electroplated diamond grinding wheel tends to flake off under the action of large grinding force, leading to rapid abrasive failure. Additionally, the electroplated diamond grinding wheel also has abrasive burn and falling off phenomenon, further reducing its service life. Therefore, from the perspective of processing performance and durability, the sintered diamond grinding wheel in grinding SiCf/SiC composite materials shows better comprehensive performance, especially under water-cooled conditions, where processing quality and stability are more advantageous.Discussion and optimization suggestionsBased on experimental data analysis, to optimize the grinding process of SiCf/SiC composites, the grinding wheel type and cooling method should be reasonably selected according to different processing stages. In the rough machining stage, the electroplated diamond grinding wheel is prone to abrasive detachment under the action of higher grinding force, so it is suitable for dry grinding condition to reduce coolant impact on abrasive particles. At the same time, it is recommended to use high speed, low feed speed and shallow grinding depth to reduce wheel wear and improve processing efficiency. In contrast, during the precision machining stage, to achieve better surface quality, it is recommended to use a sintered diamond grinding wheel combined with water-cooled grinding method to reduce the surface roughness of the workpiece, minimize micro-defects, and thus improve the surface smoothness and machining stability of the workpiece.ConclusionsThe sintered diamond grinding wheel exhibits lower grinding force and better surface quality during grinding, especially under water-cooled conditions, where its advantages are more obvious. The electroplated diamond grinding wheel is suitable for rough machining, but there is a risk of abrasive peeling and burning, which affects its service life. Therefore, in practical applications, the grinding wheels and cooling methods should be reasonably selected based on different processing requirements to improve the processing quality and the efficiency of SiCf/SiC composites. Future research can further optimize the grinding parameters and explore the effects of different grinding environments (such as micro-lubrication) on machining performance to further enhance the controllability and applicability of grinding processes.